Effect of inputs on moisture-use efficiency and productivity in greengram (Vigna radiata)under low rainfall situation - Singh, Raj; Triapthi, K P (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was conducted during 2003 and 2004 to study the effect of inputs on moisture-use efficiency, nutrients availability, crop growth and production potential of 'K 851' and 'RMG 62' varieties of greengram [Vigna radiata (L.) Wilczek]. Soil moisture-use efficiency was 21.27% higher in 'K 851' compared with the 'RMG 62'. Application of 20 kg N and 40 kg P2O5/ha increased soil moisture-use efficiency by 24.31 and 53.12%, respectively over the control plots. Seed yield was increased by 13.9% in 'K 851' than ' RMG 62'. About 11.80 and 28.10% higher seed yield was obtained due to the application of 20 kg N and 40 kg P2O5/ha as compared to control (without nutrients application), respectively. N and P uptake was significantly higher with 'K 851' and 'MG 62' whereas availability of both the nutrients in the soil was lower with 'K 851' than 'RMG 62'. The variety, N and P application also influenced nitrogen fixation in the crop. Application of 20 kg N/ha significantly increased the nitrogen and phosphorus uptake as well as nitrogen availability in the soil. Phosphorus @ 40 kg P2O5/ha significantly increased N and P uptake and P availability but N availability was remain unchanged. Net return and benefits : cost ratio were increased in 'K 851'with 20 kg N and 40 kg P2O5/ha.